2018
DOI: 10.1155/2018/4578373
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Actin Dynamics and Actin-Binding Proteins Expression in Epithelial-to-Mesenchymal Transition and Its Association with Cancer Progression and Evaluation of Possible Therapeutic Targets

Abstract: Metastasis causes death of 90% of cancer patients, so it is the most significant issue associated with cancer disease. Thus, it is no surprise that many researchers are trying to develop drugs targeting or preventing them. The secondary tumour site formation is closely related to phenomena like epithelial-to-mesenchymal and its reverse, mesenchymal-to-epithelial transition. The change of the cells' phenotype to mesenchymal involves the acquisition of migratory potential. Cancer cells movement is possible due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 127 publications
(143 reference statements)
0
86
0
2
Order By: Relevance
“…These changes depend on the reorganization of actin cytoskeleton, and actin-associated proteins control the polymerization and depolymerization processes to regulate the reorganization of actin cytoskeleton. 40 , 41 Moreover, recent studies revealed that the actin binding protein Cofilin 1 ( CFL1 ) promotes the EMT process by promoting the formation of invasive structures, as well as by modulating EMT-related gene expression via regulation of actin organization in the nucleus. 42 The present results demonstrate that FSCN1 knockdown inhibits invadopodia formation and impairs actin cytoskeleton organization.…”
Section: Discussionmentioning
confidence: 99%
“…These changes depend on the reorganization of actin cytoskeleton, and actin-associated proteins control the polymerization and depolymerization processes to regulate the reorganization of actin cytoskeleton. 40 , 41 Moreover, recent studies revealed that the actin binding protein Cofilin 1 ( CFL1 ) promotes the EMT process by promoting the formation of invasive structures, as well as by modulating EMT-related gene expression via regulation of actin organization in the nucleus. 42 The present results demonstrate that FSCN1 knockdown inhibits invadopodia formation and impairs actin cytoskeleton organization.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our study reveals a novel relationship between nuclear actin and HGPS. Recent research has shown that nuclear actin is involved in multiple diseases, including cancer and myopathy [60,61]. Understanding the molecular mechanisms of nuclear actin in diseases by using model systems could contribute to the possibility of using known actin-binding chemicals for therapeutic purposes.…”
Section: Nuclear F-actin and The Molecular Etiology Of Hgps Cellsmentioning
confidence: 99%
“… 3 5 Furthermore, in the recent years, there is also an increase of interests in actin-binding proteins (ABPs) in the different types of cells, especially in the context of cell death, migration, or cell junction stabilization. 6 8 ABPs family is the group of various proteins involved in the regulation of actin filaments’ stability, growth and disassembly (polymerization and depolymerization). 9 , 10 One of the examples of ABPs is profilin-1 (PFN1), the protein involved in actin assembly through the exchange of ADP for ATP on G-actin and transport of profilin–actin complex to barbed ends of actin filaments.…”
Section: Introductionmentioning
confidence: 99%